Retrospective Study of Analysis of Deaths Due to Burns in GMERS Medical College and Hospital, Dharpur-Patan (Medico Legal Update, 2019)
Fire, one of the pure elements forming the world and one of the elements to provide life energy to all livingbeings, sometimes turns deadly. In Forensic Medicine departments, one of the most common cases for postmortem examinations is Burns case. But it becomes difficult many a times to comment on the manner ofdeath in cases with a brief survival period. So, the currentretrospective study was undertaken at Mortuarycomplex of GMERS Medical college,Dharpur-Patan, Gujarat during the period from 1st Jan 2016 to 31stDec2017.